Subjectification of idiom introducers in discourse: the case of proverbial in English, Polish and Croatian - Stanojević, Mateusz-Milan (Array, 2012)
In the sentence "DataEase is one of those products that has hidden its light under the proverbial bushel." "proverbial" signals the use of the idiom "to hide one’s light under the bushel". This and similar discursive elements may indicate metaphors, proverbs and idioms, often signaling speaker attitude. However, in: "She knew he had the proverbial wife and two kids at Camberley." "proverbial" does not seem to signal any of these categories. Similar examples appear in Croatian with "poslovičan" ‘proverbial’ and in Polish with "przysłowiowy" ‘proverbial’. Using corpus data (COCA, HNK and IPI PAN) we argue that "proverbial", "poslovičan" and "przysłowiowy" signal various types of intersubjectively shared cultural models based on the notion of the proverb and its characteristics. They exhibit formal and semantic differences, which are a result of their subjectification (in the Langackerian sense). Non–subjectified meanings combine with non–idiomatic and non–conventional items, whereas subjectified meanings combine with idiomatic and conventional items. Their cross–linguistic variation is a result of larger grammatical patterns related to the subjectification of adjectives in the three languages.